Systematic theology. Volume 1, The triune God - Jenson, Robert W. (New York : Oxford University Press, 1997)
Jensen begins this first of two volumes with an extended discussion of the nature and norms of theology. He then devotes the rest of the work to the identity and being of the biblical God, including classic Christological and soteriological questions most systems take up elsewhere.
PART I: PROLEGOMENA -- PART II: THE TRIUNE IDENTITY -- PART III: THE TRIUNE CHARACTER
Includes bibliographical references and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Theology, Doctrinal; Trinity; Théologie dogmatique; Trinité.; RELIGION -- Christianity -- General; RELIGION -- Christian Theology -- Systematic; Trinity; Theology, Doctrinal